PENANAMAN NILAI-NILAI TAUHID MELALUI PEMBELAJARAN BAHASA ARAB - Risda, Risda; Salamuddin, Salamuddin (Universitas Al-Amien Prenduan, 2023)
Instilling Monotheistic Values in Learning Arabic. Arabic Language Education Study Program, Faculty of Tarbiyah and Teacher Training, UIN North Sumatra Medan. This study discusses instilling the values of monotheism in learning Arabic. The problem studied is what are the monotheistic values instilled in learning Arabic. This study aims to find out how students change in learning after the inculcation of monotheistic values is included in learning. This study uses library research methods, namely searching for data, collecting data and analyzing data. The results of this study indicate that there are several ways to instill the value of monotheism in learning Arabic. The reason why it is necessary to instill the value of monotheism in learning Arabic is so that students are not only experts in the cognitive field, but so that students understand that everything in this world must have something to do with Allah SWT, especially in the field of education. And also so that students have good morals and manners in their daily lives.